Evaluation of Multidisciplinary Team Clinic for Patients With Isolated Cleft Lip. (July 2020) - Padovano, William M.; Snyder-Warwick, Alison K.; Skolnick, Gary B.; Pfeifauf, Kristin D.; Menezes, Maithilee D.; Grames, Lynn M.; Cheung, Susan; Kim, Andrew M.; Cradock, Mary Michaeleen; Naidoo, Sybill D.; Patel, Kamlesh B.
Objective: To report the incidences of secondary lip and nose operations, otolaryngology procedures, speech-language therapy, neurodevelopmental concerns, and dental and orthodontic issues in children with isolated cleft lip to inform multidisciplinary cleft team protocols. Setting: An American Cleft Palate-Craniofacial Association–approved team at a tertiary academic children's hospital. Design: Retrospective cohort study of patients evaluated through longitudinal clinic visits by a multidisciplinary cleft palate and craniofacial team between January 2000 and June 2018. Patients, Participants: Children with nonsyndromic cleft lip with or without cleft alveolus (n = 92). Results: Median age at final team visit was 4.9 years (interquartile range: 2.4-8.2 years). Secondary plastic surgery procedures were most common between ages 3 and 5 (135 per 1000 person-years), and the majority of these procedures were minor lip revisions. The rate of tympanostomy tube insertion was highest before age 3 (122 per 1000 person-years). By their final team visit, 88% of patients had normal hearing and 11% had only slight to mild conductive hearing loss. No patients had speech errors attributable to lip abnormalities. Psychological interventions, learning disabilities, and dental or orthodontic concerns were uncommon. Conclusions: Most patients with isolated cleft lip may not require long-term, longitudinal evaluation by cleft team specialists. Cleft teams should develop limited follow-up protocols for these children to improve resource allocation and promote value-based care in this patient population.